Bibliometric study and visual analysis of postoperative diabetes mellitus in kidney transplant recipients based on WoSCC database - Minhua Qiu; Sheng Chen; Jibing Chen; Hongjun Gao (Renal Failure)
Background In recent years, the increase of the post-transplantation diabetes mellitus (PTDM) after renal transplantation encourages people to do a lot of research on the disease. This paper conducted a bibliometric study on PTDM related literature to explore the risk factors of diabetes after kidney transplantation, as well as the current status, hotspots and development trends of PTDM research, so as to provide reference for researchers in related fields.Methods We searched the Web of Science Core Collection (WoSCC) database for PTDM literature from January 1, 1990, to August 20, 2023, and used VOSviewer, CiteSpace, and the R package ‘bibliometrix’ to do bibliometric analysis.Results Obesity, 3 months after transplantation tacrolimus concentration >10 ng/mL, temporary hyperglycemia, delayed graft function, acute rejection is specific risk factors related to PTDM in renal transplant recipients. In addition, 74 countries led by China and the United States published 1546 papers, and the number of PTDM-related publications is increasing every year. Primary institutions included the University of California, Los Angeles, Mayo Clinic, University of Oslo, and University of Toronto. The Journal of Transplantation is the most widely read journal in the subject. The authors with the most published literature are Trond Jenssen and Adnan Sharif, and the most cited author is Kasiske BL. Expectations for continued growth in global PTDM research are increasingly high. Future studies will mainly focus on exploring the risk factors of PTDM and identifying new therapeutic approaches and targets.